Vlog as a Media in the Students’ Speaking Skills Development: A Classroom Action Research Study - Bolang, Rinaldo Paulus; Nurkhamidah, Neni (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research study investigated the impact of the use of vlog as a media on the students’ speaking skills development. The objective of this research is to determine whether there is a significant development in the implementation of vlog as media in the students’ speaking skills or not. This is a Classroom Action Research (CAR), conducted in SMKN 6 Jakarta with 17 participants (students) in a classroom. The participants are X-grade students of animation. This research study used two cycles to find the students’ speaking skills development. The findings show that the mean score from pre-test up to post-test increased each. Post-test (79) mean score is higher than the pre-test (61). This indicates that there is a significant difference between pre-test and post-test after conducting this PBL.